The dynamics of income inequality in Africa: An empirical investigation on the role of macroeconomic and institutional forces. (September 2022) - Batuo, Michael E.; Kararach, George; Malki, Issam
Highlights: This study confirms previous findings that income across Africa is overall divergent and forms clubs of convergence: high income, middle income and low-income clubs. Findings suggest that the Kuznets' curve relationship holds only for economies at the bottom of income distribution. Inequality is found to be increasing in high income countries in Africa. There is a limited role of macroeconomic and institutional factors in explaining income inequality in low-income economies. Fiscal, employment and monetary policies and the rule of law play a statistically significant role in tackling inequality in high-income economies. Abstract: Reducing income inequality is a crucial goal of sustainable development as income inequality often viewed as harmful to economic growth. The main aim of this paper was to empirically assess the macroeconomic and institutional drivers of income inequality in Africa. We use a Kuznets curve framework, which emphasises the role of income per capita in explaining the time path of inequality. In contrast to much of the literature, we explicitly examine the possibility of the existence of multiple income steady states. Using the concept of clubs of convergence, we show that per capita income is divergent and identify four steady states to which groups of economies converge (i.e., high-income to low-income economies). Using panel data models and a data set encompassing 52 African countries spanning the years 1980–2017, we show that once these multiple steady states are accounted for, the Kuznets curve relationship becomes unstable. Our findings suggest that inequality may be increasing in high-income countries in Africa, while decreasing in low-income or the least developed economies. In addition, the role of macroeconomic and institutional factors in explaining income inequality is limited and differ across convergence clubs. Evidence suggests the importance of fiscal, employment and monetary policies and the rule of law to tackle inequality in high-income economies, while they have no statistically significant role in low-income economies' income inequality.